Linear Space Requirements and Perch Use of Conventional Layer Hybrids and Dual-Purpose Hens in an Aviary System - Giersberg, Mona F.; Spindler, Birgit; Kemper, Nicole (Frontiers in Veterinary Science, 2019)
Roosting on elevated perches is a behavioural priority in laying hens, which is well investigated in both experimental and commercial settings. However, little is known about perching behaviour and perch requirements of alternative hybrids, such as dual-purpose hens. The aim of the present study was to gain basic knowledge on linear space requirements and perching patterns of dual-purpose hens (Lohmann Dual, LD) by comparing them to a conventional layer line (Lohmann Brown plus, LB+). About 3700 hens per genetic strain were housed in two consecutive batches in four compartments of an aviary system with metal perches at different heights above a grid tier. As an indicator for required perching space, the body widths of a sample of individual hens was determined by image analyses. In addition, the use of five differently located perches and one cross-brace (structural element of the aviary system) was assessed by photo-based observations during the light and the dark phase. The LD hens measured an average body width of 15.95 ± 0.08 cm, and thus occupied about 7% more linear space than the LB+ hens (14.77 ± 0.08 cm body width; P < 0.05). Overall perch use was higher during the dark compared to the light phase, both in the LB+ (3.89±0.08 hens/m vs. 0.79±0.03 hens/m, P < 0.05) and the LD hens (2.88±0.06 hens/m vs. 0.86±0.03 hens/m, P < 0.05). With a maximum of 8.17 hens/m, the LB+ hens preferred to roost on the highest perches available at night. In contrast, the LD hens also rested on the lowest perches, and showed a more even use of all perches provided. During the day, the LD hens seemed to need lower perches for easy access to the feeders, whereas more LB+ hens used the higher perches, presumably to avoid threatening conspecifics. The present results show that preferences for certain perch locations differed between conventional layers and dual-purpose hens, whereas diurnal patterns of perch use were similar in both hybrids. Therefore, perches should be designed and located in an aviary system to meet the specific preferences and behavioural needs of the hybrid housed.